Experimental Investigation on Mechanical Joint of Lontar (Borassus Flabellifer) Fiber Reinforced Polyester Composites under Static Flexural Test - Bale, Jefri S; Pell, Yeremias M; Jafri, Muhamad; Selan, Rima (Indonesian Journal of Science and Technology, 2019)
This study has been conducted to investigate the flexural strength of Borassus Flabellifer Fiber/BFF reinforced polyester composite joint under static condition. Tests were carried out to study the flexural strength of double strap butt joint and single lap joint of BFF polyester composite. In addition, post observation of macroscope was used to map failure behavior. The results shown that the flexural strength of single lap joint is higher compared to double strap butt joint ofÂ  BFF polyester composite. The larger cross-sectional area and the existence of gap area could be the main reason for lower flexural strength generated by double strap butt joint ofÂ  BFF polyester composite. The failure of BFF polyester composite joints under flexural test indicated the brittle failure behaviour that fiber breakage was found to be the final failure mechanism which start with matrix cracking and fiber-matrix debonding failure mechanisms.